Energy and Environmental Refurbishment of the Hygiene Institute within the Sapienza University of Rome campus. Issue 1 (1st December 2022) - Romano, G; Martellucci, G; Mancini, F; Battisti, A
Abstract: Starting from the definition of sustainable development introduced by the 2030 Agenda, and the most recent European implementation tools such as above all the New Green Deal, three goals have been highlighted as pilot objectives of this research: Goal 13 "Climate Action" to strengthen the resilience and adaptability of our building stock to climate-related risks, Goal 7 "Affordable and Clean Energy" by increasing the share of renewable energy and improving the energy efficiency of the existing building stock and Goal 6 "Clean Water and Sanitation", aimed, in this specific case, at a sustainable management of water resources and technologies for recycling and reuse. In particular, the research work focused on the energy and environmental redevelopment, from a green perspective, of the "Sanarelli" Institute of Hygiene within the "Sapienza" University of Rome campus. The building was built in 1935 and, following a series of changes over the years, currently has a total volume of 37, 700 m 3 and an area of 9, 475 m 2 . After an in-depth study of the status quo thanks to inspections, surveys, non-invasive investigations and environmental analyses, the work has focused on the definition of specific objectives with the ultimate aim of the energy and environmental refurbishment intervention by tracing 7 strategies thanks to which it has been possible to identify 9 technical solutions to be applied to the Institute. The design choices highlight a close synergy between active and passive devices which together contribute to achieving a circular use of water resources on site, with systems for capturing and collecting rainwater and treating wastewater, as well as achieving a significant improvement in the energy behaviour of the building. This improvement has been possible not only thanks to the updating, with respect to nowadays uses and standards, of the characteristics of the building envelope and of the active systems, but also thanks to the close collaboration between the active and passive technological solutions that have led to satisfactory results with a view to reducing CO2 emissions.